2010
DOI: 10.1590/s1519-69842010000600010
|View full text |Cite
|
Sign up to set email alerts
|

Are the streams of the Sinos River basin of good water quality? Aquatic macroinvertebrates may answer the question

Abstract: Macroinvertebrate communities are one of the most used groups in assessments of water quality, since they respond directly to the level of contamination of aquatic ecosystems. The main objective of this study was the assessment of the water quality of the Sinos River basin (Rio Grande do Sul state, Brazil) through biotic indices based on the macroinvertebrate community ("Family Biotic Index -FBI", and "Biological Monitoring Working Party Score System -BMWP"). Three lower order streams (2 nd order) were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…River basin represent 68% of the total amount registered for the state of Rio Grande do Sul. Bieger et al (2010), registered 54 macroinvertebrate families in small streams in the Sinos River basin. For these 54 families, the following were not registered in this study: Mycetopodidae and Sphaeridae (Bivalvia/Mollusca) and Lymnaeidae and Physidae (Gastropoda/Mollusca); Dogielinotidae (Arthropoda/Crustacea/Amphipoda) and Aeglidae (Arthropoda/Crustacea/Decapoda); Aeshnidae (Arthropoda/Insecta/Odonata); Noteridae (Arthropoda/ Insecta/Coleoptera); Euthyplocidae (Arthropoda/Insecta/ Ephemeroptera); Nepidae, Hydrometridae, Gelastocoridae and Corixidae (Arthropoda/Insecta/Hemiptera); Dixidae, Ceratopogonidae and Blephaceridae (Arthropoda/Insecta/ Diptera).…”
Section: Biodiversity Community Structure and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…River basin represent 68% of the total amount registered for the state of Rio Grande do Sul. Bieger et al (2010), registered 54 macroinvertebrate families in small streams in the Sinos River basin. For these 54 families, the following were not registered in this study: Mycetopodidae and Sphaeridae (Bivalvia/Mollusca) and Lymnaeidae and Physidae (Gastropoda/Mollusca); Dogielinotidae (Arthropoda/Crustacea/Amphipoda) and Aeglidae (Arthropoda/Crustacea/Decapoda); Aeshnidae (Arthropoda/Insecta/Odonata); Noteridae (Arthropoda/ Insecta/Coleoptera); Euthyplocidae (Arthropoda/Insecta/ Ephemeroptera); Nepidae, Hydrometridae, Gelastocoridae and Corixidae (Arthropoda/Insecta/Hemiptera); Dixidae, Ceratopogonidae and Blephaceridae (Arthropoda/Insecta/ Diptera).…”
Section: Biodiversity Community Structure and Compositionmentioning
confidence: 99%
“…The following studies are highlighted for the drainage basin of the Sinos river: Mansur and Pereira (2006), Strieder et al (2006), Bieger et al (2010) and Maltchik et al (2010). The objective of the present study is to characterize the benthic macroinvertebrate fauna found in three water bodies located in the Sinos river drainage basin regarding community structure.…”
Section: Introductionmentioning
confidence: 99%
“…The main anthropogenic factors in the area are the agricultural activity in the upper reach, the leather and footwear industry and the increase of the population density in the middle reach, and a high population density and the presence of leather and footwear industry, metallurgy and petrochemical plants in the lower reach (Bieger et al, 2010;Figueiredo et al, 2010;FEPAM, 2012;Nunes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Macroinvertebrate assemblage measures are considered as effective and reliable indicators for environmental degradation and overall river health (e.g. Thorne and Williams, 1997;Smith et al, 1999;Bieger et al, 2010). Relative to European and American river systems, subtropical Asian rivers support rich but poorly known macroinvertebrate communities (Morse et al, 2007).…”
Section: Introductionmentioning
confidence: 99%